Meeting the Accreditation Standard for Diversity. Issue 1 (23rd March 2023) - Snyder, Jennifer; Hills, Karen; Alexander, Lisa; Statler, Michel; Straker, Howard; Bowser, Jonathan; Alesbury, Elizabeth
Abstract: While increasing diversity has been an ongoing concern in physician assistant (PA) education, there is now a concentrated focus on diversity, equity, inclusion, and social justice, elevating these to top priorities. To achieve the goal of diversifying the PA workforce, PA programs, with their institution's support, must systematically inculcate strategies for overcoming and dismantling barriers against students of color and students underrepresented in medicine (URiM). These strategies should disrupt the status quo and expand structural processes that ensure successful diversification of students, especially URiM students, LGBTQ students, students from medically underserved areas, and first-generation college students.